Requirements and effects of vitamin c and e on non-specific immune responses and disease resistance in hybrid grouper epinephelus fuscoguttatus x e. Lanceolatus - Isabella Ebi (2019)
Hybrid grouper of E fuscoguttatus x E /anceolatus is popular in Southeast Asia due to their high growth rate, good price, and demand in the live fish trade market. Despite the advantages, there is very limited information on the nutritional requirements of the hybrid grouper and so far, there is no information on their vitamins C and E requirements. Vitamins C and E are well known for their function in boosting the immune responses in fish and improve fish growth. Bacteria especially Vibrio harveyi is one of the pathogens that cause a disease outbreak in marine fish species. Therefore, the present study was carried out to determine the vitamins C and E requirements and their effects on non-specific immune responses and disease resistance against II. harveyi in hybrid grouper. In Trial 1, eight experimental diets containing different vitamin C (0, 12, 24, 47, 76, 95, 156, and 303 mg/kg) levels in the form of L-ascorbic acid (AA) were fed to triplicate group of fish with initial weight of 7.7±0.lg and cultured in flow-through seawater system for 10 weeks. The results show that the highest final body weight (FBW), body weight gain (BWG) and specific growth rate (SGR) were achieved by the fish fed diet supplemented with 156 mg AA/kg. In this study, supplementation of vitamin C did not significantly affect the survival of fish. However, fish groups fed with the diet of less than 95 mg AA/kg show skeletal deformities (fusion, lordosis, kyphosis, and scoliosis). In Trial 2, eight experimental diets containing different vitamin C (0, 18, 45, 76, 142, 241, 377, and 768 mg/kg) levels in the form of L-ascorbyl acid 2-polyphosphate (C2PP) were fed to a triplicate group of fish with an initial weight of 10.4±0.lg. After 14 weeks of the feeding trial, the results show highest FBW, BWG, SGR were achieved by the fish fed diet supplemented with 18 mg C2PP/kg. In Trial 3, seven experimental diets containing different vitamin E (10, 34, 61, 122, 232, 416, and 815 mg/kg) levels in the form of alpha tocopherol acetate were fed to a triplicate group of fish with an initial weight of 7.74±0.lg for 10 weeks. The results show that the highest FBW, BWG, and SGR were achieved by the fish fed diet supplemented with 110 mg vitamin E/kg. Higher level of vitamin E supplementation (815 mg/kg) is needed to reduce thiobarbituric acid reactive substances (TSARS) in fish tissues and enhance disease resistance when infected with II. harveyi. In Trial 4, fish were fed with six experimental diets containing different levels of C2PP [no supplementation (-), optimum(+), and high(++)] and vitamin E [no supplementation(-), low 0), and optimum ( + )]. Significant lower survival and growth performance were observed in fish fed no C2PP and vitamin E supplementation diet (-C-E: -ve Control). Meanwhile, fish fed higher level of C2PP and no vitamin E supplementation ( ++C-E) (contained 271.8 C2PP and 13.4 vitamin E mg/kg, respectively) shows comparable survival, growth, and disease resistance to the fish fed diet supplemented with optimum level of C2PP and vitamin E ( +C+E: +ve Control) (contained 18.3 C2PP and 814.8 vitamin E mg/kg, respectively). In conclusion, a combination of 18.3 mg/kg C2PP and 814.8 mg/kg vitamin E or 271.8 mg/kg C2PP and 13.4 mg/kg vitamin E dietary supplementation is recommended to produce healthy fish with optimum growth. Additionally, a higher supplementation level of vitamin C is able to spare vitamin E in the diet for hybrid grouper.